Eptinezumab Demonstrated Efficacy in Sustained Prevention of Episodic and Chronic Migraine Beginning on Day 1 After Dosing. Issue 10 (9th November 2020) - Dodick, David W.; Gottschalk, Christopher; Cady, Roger; Hirman, Joe; Smith, Jeff; Snapinn, Steve
Abstract : Objective: To determine the onset of preventive efficacy with eptinezumab in patients with migraine. Background: Eptinezumab is a monoclonal antibody inhibiting calcitonin gene‐related peptide approved as an intravenously administered treatment for the prevention of migraine. Methods: Patients who received eptinezumab 100 mg, eptinezumab 300 mg, or placebo in PROMISE7‐1 (episodic migraine; 100 mg, n = 221; 300 mg, n = 222; placebo, n = 222) or PROMISE7‐2 (chronic migraine; 100 mg, n = 356; 300 mg, n = 350; placebo, n = 366) were included. Testing of the percentage of patients with a migraine on day 1 after dosing was prespecified and alpha‐controlled. In further exploration of this prespecified endpoint, a post hoc closed testing procedure, which controlled the false‐positive (type 1) error rate, provided a statistically rigorous evaluation of migraine prevention onset. The procedure involved up to 84 tests of significance, all of which were performed in sequence until the first nonsignificant result. Results: For both studies, all tests for significance for eptinezumab 100 and 300 mg, from days 1‐84 through day 1 alone, achieved nominal significance ( P  < .05), indicating that eptinezumab was fully effective beginning on day 1. Over each interval, the treatment effect was comparable to the effect over weeks 1‐12. Mean changes from baseline in monthly migraine days for the primary endpoint period ranged from −3.9 to −4.9, −4.1 to −4.9, and −2.2 to −3.2 for eptinezumab 100, 300 mg, and placebo, respectively, in PROMISE7‐1 and from −7.2 to −8.0, −7.9 to −8.2, and −4.3 to −5.6, respectively, in PROMISE7‐2. The difference from placebo (95% confidence interval) in day 1 treatment effect was −2.2 (−4.1, −0.3) and −2.5 (−4.4, −0.6) days/month for eptinezumab 100 and 300 mg, respectively, in PROMISE7‐1, and was −3.8 (−5.6, −2.0) and −4.0 (−5.8, −2.1) days/month for 100 and 300 mg, respectively, in PROMISE7‐2. Conclusions: The migraine preventive effect of eptinezumab is rapid and sustained in patients with episodic or chronic migraine, with onset of optimal preventive efficacy observed on the day following the initial dose.